Isolation, identification, and characterisation of the malachite green detoxifying bacterial strain Bacillus pacificus ROC1 and the azoreductase AzrC - Shanza Bibi; Callum W. Breeze; Vusqa Jadoon; Anum Fareed; Alina Syed; Rebecca L. Frkic; Habiba Zaffar; Muhammad Ali; Iftikhar Zeb; Colin J. Jackson; Tatheer Alam Naqvi (Scientific Reports)
Abstract Malachite green (MG) is used as a dye for materials such as wood, cotton, and nylon, and is used in aquaculture to prevent fungal and protozoan diseases. However, it is highly toxic, with carcinogenic, mutagenic, and teratogenic properties, resulting in bans worldwide. Despite this, MG is still frequently used in many countries due to its efficacy and economy. MG is persistent in the environment and so requires degradative intervention. In this work we isolated Bacillus pacificus ROC1 strain from a salt flat in Pakistan that had the ability to aerobically detoxify MG, as determined by bacterio- and phyto-toxicity assays. We demonstrate immobilized B. pacificus ROC1 can effectively detoxify MG, which highlights a potential method for its biodegradation. Genomic sequencing identified three candidate azo-reductases within B. pacificus ROC1 that could be responsible for the MG-degrading activity. These were cloned, expressed and purified from Escherichia coli, with one (AzrC), catalyzing the reduction of MG to leuco-MG in vitro. AzrC was crystallised and MG was captured within the active site in a Michaelis complex, providing structural insight into the reduction mechanism. Altogether, this work identifies a bacterium capable of aerobically degrading a major industrial pollutant and characterizes the molecular basis for this activity.